Asset auctions, information, and liquidity - Xavier Vives (Center for Economic Studies and ifo Institute (CESifo), 2010)
A model is presented of a uniform price auction where bidders compete in demand schedules; the model allows for common and private values in the absence of exogenous noise. It is shown how private information yields more market power than the levels seen with full information. Results obtained here are broadly consistent with evidence from asset auctions, may help explain the response of central banks to the crisis, and suggest potential improvements in the auction formats of asset auctions.
Keywords: D44; D82; G14; E58; 330; adverse selection; market power; reverse auctions; bid shading